Հայաստանի պետական լրատվական գործակալության հիմնադրումն ու գործունեությունը (1918–1920 թթ.) - Հրայր Զորյան (ՀՀ ԳԱԱ հրատ.)
Законом, принятым Национальным советом Армении 18 декабря 1918 г., было основано первое армянское государственное информационное агентство – Армянское телеграфное агентство (АрмТАГ). До этого информационное обеспечение независимой страны, с некоторыми ограничениями, осуществляла специальная служба – Информбюро, созданная 3 июля 1918 г. решением Национального совета Армении при армянской дипломатической миссии в Грузии и ставшая прототипом АрмТАГ-а, содействуя формированию последнего. The First Armenian State Media Agency – the Armenian Telegraphic Agency (ArmTAG) was founded by the law passed at the National Council of Armenia as of December 18, 1918. Before that, the special service – the Information Bureau, created adjunct to the Armenian Diplomatic Mission in Georgia by the decision of 3 July 1918 of the National Council of Armenia implemented the provision of media of the newly independent country with certain limitations and became the prototype of the ArmTAG, promoting the formation and establishment of the latter.
Keywords: History; Bibliography; Modern History; Language and Literature; Information resources; D History; PNJ Journalism; The periodical Press, etc